Ras-Related Protein Rab5a Regulates Complement C5a Receptor Trafficking, Chemotaxis, and Chemokine Secretion in Human Macrophages - Kai-Chen Wu; Nicholas D Condon; Timothy A. Hill; Robert C. Reid; David Fairlie; Junxian Lim (Journal of Innate Immunity, 2023)
Complement activation and Rab GTPase trafficking are commonly observed in inflammatory responses. Recruitment of innate immune cells to sites of infection or injury and secretion of inflammatory chemokines are promoted by complement component 5a (C5a) that activates the cell surface protein C5a receptor1 (C5aR1). Persistent activation can lead to a myriad of inflammatory and autoimmune diseases. Here, we demonstrate that the mechanism of C5a induced chemotaxis of human monocyte-derived macrophages (HMDMs) and their secretion of inflammatory chemokines are controlled by Rab5a. We find that C5a activation of the G protein coupled receptor C5aR1 expressed on the surface of HMDMs, recruits β-arrestin2 via Rab5a trafficking, then activates downstream phosphatidylinositol 3-kinase (PI3K)/Akt signaling that culminates in chemotaxis and secretion of pro-inflammatory chemokines from HMDMs. High-resolution lattice light-sheet microscopy on live cells showed that C5a activates C5aR1-GFP internalization and colocalization with Rab5a-tdTomato but not with dominant negative mutant Rab5a-S34N-tdTomato in HEK293 cells. We found that Rab5a is significantly upregulated in differentiated HMDMs and internalization of C5aR1 is dependent on Rab5a. Interestingly, while knockdown of Rab5a inhibited C5aR1-mediated Akt phosphorylation, it did not affect C5aR1-mediated ERK1/2 phosphorylation or intracellular calcium mobilization in HMDMs. Functional analysis using transwell migration and µ-slide chemotaxis assays indicated that Rab5a regulates C5a-induced chemotaxis of HMDMs. Further, C5aR1 was found to mediate interaction of Rab5a with β-arrestin2 but not with G proteins in HMDMs. Furthermore, C5a-induced secretion of pro-inflammatory chemokines (CCL2, CCL3) from HMDMs was attenuated by Rab5a or β-arrestin2 knockdown or by pharmacological inhibition with a C5aR1 antagonist or a PI3K inhibitor. These findings reveal a C5a-C5aR1-β-arrestin2-Rab5a-PI3K signaling pathway that regulates chemotaxis and pro-inflammatory chemokine secretion in HMDMs and suggests new ways of selectively modulating C5a-induced inflammatory outputs.